Indonesia's Foreign Policy Towards Malaysia And Thailand Regarding Rohingya Refugees In Indonesia During The Early Years Of President Joko Widodo's Administration - Mohamad Rifai (Universitas Budi Luhur, 2024)
Abstrak: Penelitian ini bertujuan untuk menyelidiki bagaimana Indonesia menanggapi Malaysia dan Thailand terkait pengungsi Rohingya selama awal kepemimpinan Presiden Joko Widodo. Dalam menganalisis permasalahan ini, konsep pengungsi dan politik luar negeri digunakan sebagai kerangka penelitian. Pendekatan kualitatif diambil dengan menggunakan data sekunder. Hasil penelitian menunjukkan bahwa politik luar negeri Indonesia menerapkan pendekatan multilateral dengan mengadakan pertemuan bersama negara asal, negara transit, dan negara tujuan untuk mengatasi masalah migran tidak teratur, khususnya dengan Malaysia dan Thailand. Indonesia memutuskan untuk secara aktif berpartisipasi dalam pertemuan yang diselenggarakan oleh Malaysia, Thailand, dan Indonesia sendiri. Meskipun pertemuan tersebut tidak sepenuhnya menyelesaikan permasalahan pengungsi Rohingya di Indonesia, namun setidaknya membantu mengurangi jumlah pengungsi Rohingya yang memasuki wilayah perairan Indonesia. Selain itu, bantuan yang diberikan oleh Amerika Serikat dalam pertemuan di Bangkok turut berkontribusi dalam memenuhi kebutuhan dasar pengungsi Rohingya di Aceh. Abstract: This study aims to explore Indonesia's diplomatic approach towards Malaysia and Thailand concerning Rohingya refugees in Indonesia during the early tenure of President Joko Widodo. To analyze this issue, the research employs the concepts of refugees and foreign policy. Utilizing secondary data, this qualitative study reveals that Indonesia's foreign policy adopts a multilateral strategy by engaging in meetings with countries of origin, transit, and destination to address the challenges of irregular migration, particularly with Malaysia and Thailand. Indonesia opted to actively participate in meetings organized by the governments of Malaysia and Thailand and its own government. Although these meetings did not entirely resolve the issues related to Rohingya refugees in Indonesia, they contributed to alleviating the problem by reducing the influx of Rohingya refugees into Indonesian waters. Furthermore, the assistance provided by the United States during the Bangkok meeting played a role in meeting the basic needs of Rohingya refugees in Aceh.